Spain : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Spain. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2022)
The Spanish economy is recovering from the deep recession caused by the COVID pandemic and employment is already above its pre-pandemic level. A highly successful vaccination campaign helped limit the impact of the recent wave of infections on hospitalizations and economic activity. Output is expected to return to its pre-pandemic level by the end of 2022. However, there is significant uncertainty around the recovery path related to the evolution of the pandemic and the duration of global supply bottlenecks. The pace of absorption and the effectiveness of use of Next Generation EU (NGEU) funds will also affect growth in the coming years. In the near term, the key policy challenge is to continue to provide targeted pandemic support while facilitating resource reallocation and a transformation to a greener and more inclusive economy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy